Análise sobre o uso dos contos de fadas na zona ribeirinha no município de Abaetetuba-PA - MAUÉS, Diana Teles (2019)
Authors such as Cosson (2016); Kleiman (2003); Brandão (1997); Foucambert (1997), among others, hold discussions that emphasize the importance of reading the literary text to the process of literary literacy development, since these enable the subjects to develop socio-cognitive skills. Cosson (2016) points out that by reading the literary texts it is possible to adopt a behavior and a language acquiring the taste for reading without losing the "bonitoza" of the texts. In this line of thinking, the reading of the literary text can be a practice focused on sociocultural reflection, through experiences. In this way, it is known that the reading of literary texts is important for the development of literacy, however, often, there is only the affirmation of this importance without it being clear how and under what conditions these texts exert this formative role. That is, it is necessary to advance in these studies in order to answer the following questions: how and why do fairy tales and / or literary texts promote literary literacy? What are these texts that make them so important to the process of literary literacy? Thus, through this study, we aim to analyze how the use of Fairy Tales of the Grimm brothers promotes literary literacy, reflecting on the interactionist linguistic sociocognitive functions in human development. The present study is theoretical, based on the theoretical production of authors such as Silva, Lajolo, legal documents such as NCPs, among others, representative of this thematic approach. The results of this research point out that the use of Fairy Tales and the reading of the literary text play fundamental sociocognitive roles to the development of the literary reader, because through these is possible to exercise mainly the imagination, feelings as a sense of solidarity, and a critical reflection on everyday situations. Also, by using these resources as a tool for literacy, you can broaden your knowledge about the world. From the pedagogical point of view, the role of the teacher in this process is essential, since he can create situations with several possibilities of re-reading the different themes of Fairy Tales, so that the subject can read beyond what is offered by his daily life, thus expanding his knowledge of the world.